The Relationship Between Stress Levels And Adaptability In New Students At Integrated SMP Ar-Risalah Boarding School - Ramadhan, Jhidan; Rosmiati, Rosmiati; Nur Fauziyah, Diny (LPPM STIKes Muhammadiyah Ciamis, 2025)
Purpose: This study aims to determine whether there is a relationship between stress levels and adaptability among new students at the Integrated Islamic Boarding School SMP Ar-Risalah. Methods: This research employs a quantitative method with a cross-sectional approach. The sampling technique used in this study is random sampling, applying the Slovin formula. A total of 77 respondents were obtained after calculating the sample size using the Slovin formula. Data were analyzed using the chi-square statistical test. Results: The study findings indicate a relationship between stress levels and adaptability among new students at the Integrated Islamic Boarding School SMP Ar-Risalah. The highest stress level category, classified as severe stress, was experienced by 34 respondents (44.2%), while the lowest stress level, categorized as mild stress, was observed in 10 respondents (13.0%). Additionally, the highest adaptability category was maladaptive, with 52 respondents (67.5%), whereas the lowest category, adaptive, was recorded in 25 students (32.5%). Conclusion: The analysis results show a significant relationship between stress levels and adaptability among new students at the Integrated Islamic Boarding School SMP Ar-Risalah.